GALLANT BRITISH-INDIANS, VIOLENT INDONESIANS: BRITISHINDONESIAN CONFLICT IN TWO BRITISH NEWSPAPERS, THE FIGHTING COCK AND EVENING NEWS (1945-1946) - Zara, Muhammad Yuanda (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2015)
No longer after Sukarno proclaimed Indonesian independence, British and Indian troops were deployed in Indonesia to disarm Japanese troops and evacuate prisoners of war and internees. British arrival was initially welcomed by nationalist Indonesians. Yet, clashes with armed Indonesians occured when the British were considered by nationalist Indonesians as supporting the restoration of Dutch colonial power. In order to campaign their policies, British military in Jakarta published two English languange newspapers, The Fighting Cock dan Evening News. This article analyzes how both newspapers were run and how they reported political and military developments in Indonesia. The main themes I explore are reports about the newspapers justification on British presence in Indonesia, violence committed by Indonesians, British and Indian troops' heroism, and the British troops' victories.Tidak lama setelah Sukarno memproklamasikan kemerdekaan Indonesia, pasukan Inggris dan India dikirim ke Indonesia untuk melucuti pasukan Jepang dan menyelamatkan tawanan perang dan interniran. Awalnya kedatangan Inggris disambut baik oleh golongan nasionalis Indonesia. Namun, pertempuran dengan pihak Indonesia mulai terjadi saat Inggris dianggap mendukung kembalinya kolonialisme Belanda. Dalam rangka mengkampanyekan kebijakan-kebijakannya, militer Inggris di Jakarta menerbitkan dua surat kabar, yakni The Fighting Cock dan Evening News. Tulisan ini menganalisa bagaimana kedua surat kabar tersebut dikelola dan bagaimana mereka melaporkan berbagai perkembangan politik dan militer di Indonesia. Tema utama yang dibahas adalah bagaimana laporan mereka menjustifikasi kehadiran Inggris di Indonesia, kekerasan yang dilakukan pihak Indonesia, heroisme pasukan Inggris dan India, dan kemenangan yang diraih pasukan Inggris.